Hematological and Anthropometric features of patients with Knee Osteoarthritis (Bangladesh Journal of Medical Science, 2022)
Objectives:Osteoarthritis (OA) is leadingcauseof decline in physical activity. The study objectiveswere to evaluate hematological and anthropometric features in knee OA.Methodology: This case control study from March 2019 to August 2019 on patients attending general outpatient department ofNaz MemorialHospital Karachi. Patients above 18 years of either gender, diagnosed as either knee OA on X-ray knee were included. Patients with positive family history,heavy lifting workers, and women on hormonal replacement therapy were excluded. SPSS version 23.0 was used for data analysis. Chi-square test was applied OA and control group keeping p-value of